Stable zero-dimensional cesium indium bromide hollow nanocrystals emitting blue light from self-trapped excitons. (June 2021) - Zhang, Fei; Yang, Dongwen; Shi, Zhifeng; Qin, Chaochao; Cui, Minghuan; Ma, Zhuangzhuang; Wang, Lintao; Wang, Meng; Ji, Xinzhen; Chen, Xu; Wu, Di; Li, Xinjian; et al.
Highlights: Zero-dimensional Cs3 InBr6 NCs with intrinsic blue emission were firstly demonstrated. Joint experiment-theory studies confirm the self-trapped excitons emission behavior. Solid-to-hollow conversion of NCs was realized by controlling Ostwald ripening rate. The easy diffusion of Br vacancy in lattice assist the formation of hollow structure. The hollow Cs3 InBr6 NCs demonstrate remarkable structural and optical stability. Graphical Abstract: ga1 Abstract: The growing demand for lighting and displays has motivated intensive research in metal-halide perovskite nanocrystals (NCs) recently. However, the development of blue-emissive perovskite NCs lag behind those of green and red ones severely; moreover, the conventional lead-halide perovskites contain toxic element lead. In this study, zero-dimensional Cs3 InBr6 NCs with intrinsic broadband blue emission (~ 450 nm) were developed for the first time. Joint experiment-theory characterizations reveal the excited-state structural distortion of [InBr6 ] 3− cluster enables the formation of self-trapped excitons, which contribute the broadband emission. Apart from the solid structure, hollow NCs with controlled particle and pore sizes were obtained resulting from the Ostwald ripening mechanisms. Theoretical calculations show that the easy diffusion of Br vacancies in Cs3 InBr6 lattices assist the formation of hollow structure. Encouraged by the remarkable structural and optical stability of hollow Cs3 InBr6 NCs, such lead-free NCs may open up new avenues for manufacture of optoelectronic devices.